Profile of Bioactive Compounds, Aromas, and Cup Quality of Excelsa Coffee (Coffea liberica var. dewevrei) Prepared from Diverse Postharvest Processes - Dian Herawati; Michael Oscarius Loisanjaya; Radwa Husni Kamal; Dede Robiatul Adawiyah; Nuri Andarwulan (International Journal of Food Science)
The study is aimed at evaluating bioactive compounds, volatile compounds, and cup quality of Excelsa coffee (Coffea liberica var. dewevrei) from different postharvest processing procedures, i.e., natural, honey, semiwashed, and wine. The green beans from each procedure were roasted at light to medium levels. Sample analysis was performed using HPLC and GC-MS instruments for bioactive compounds and volatile compounds, respectively, followed by a cupping test. As the results, postharvest processing significantly altered content of bioactive compounds (caffeoylquinic acids (CQAs) and alkaloids) in Excelsa green beans; the lowest quantity of CQAs and alkaloids was found in wine and semiwashed green beans, respectively. Significant degradation of 5-CQA and its transformation to 3-CQA and 4-CQA occurred in all light-medium roasting levels. In general, alkaloids were stable during roasting, and only trigonelline was slightly declined. Roasting process also generated 17 potent volatile compounds in Excelsa beans including 2-ethylpyrazine, 2,3-dimethylpyrazine, 2,5-dimethylpyrazine, 2,5-dimethyl-3-ethylpyrazine, guaiacol, 4-vinyl-guaiacol, and isovaleric acid and its esters. Furthermore, cupping test revealed that Excelsa coffee samples obtained from different postharvest processing were categorized as very good coffee (cupping score>80). This finding may encourage the commercialization of all observed Excelsa coffee beans.